165k views
25 votes
'() if () = (sin )cos 0 < <​

User Efemoney
by
5.3k points

1 Answer

9 votes

Answer:


\:f'\left(x\right)=\cos \:\left(2x\right)

Explanation:

Given the function


\:f\left(x\right)=\left(sinx\right)cosx

Let us take the derivative


(d)/(dx)\left(\sin \left(x\right)\cos \left(x\right)\right)

Apply the product rule:
\left(f\cdot g\right)'=f\:'\cdot g+f\cdot g'

so


(d)/(dx)\left(sinx\right)cosx\:=(d)/(dx)\left(\sin \:\left(x\right)\right)\cos \:\left(x\right)+(d)/(dx)\left(\cos \:\left(x\right)\right)\sin \:\left(x\right)

as


(d)/(dx)\left(\sin \:\left(x\right)\right)=cos\left(x\right)


(d)/(dx)\left(cos\:\left(x\right)\right)=-sin\:\left(x\right)

so


=\cos \left(x\right)\cos \left(x\right)+\left(-\sin \left(x\right)\right)\sin \left(x\right)


=\cos ^2\left(x\right)-\sin ^2\left(x\right)

Use the following identity:
\cos ^2\left(x\right)-\sin ^2\left(x\right)=\cos \left(2x\right)


=\cos \left(2x\right)

Therefore,


\:f'\left(x\right)=\cos \:\left(2x\right)

User Uem
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.